2014
DOI: 10.1105/tpc.114.129759
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Golgi Network-Located AP1 Gamma Adaptins Mediate Dileucine Motif-Directed Vacuolar Targeting in Arabidopsis

Abstract: Membrane proteins on the tonoplast are indispensible for vacuolar functions in plants. However, how these proteins are transported to the vacuole and how they become separated from plasma membrane proteins remain largely unknown. In this study, we used Arabidopsis thaliana vacuolar ion transporter1 (VIT1) as a reporter to study the mechanisms of tonoplast targeting. We showed that VIT1 reached the tonoplast through a pathway involving the endoplasmic reticulum (ER), Golgi, trans-Golgi network (TGN), prevacuola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 90 publications
(144 reference statements)
0
93
0
Order By: Relevance
“…The Arabidopsis genome encodes putative subunits of all five AP complexes (Happel et al, 2004;Hirst et al, 2011;Park et al, 2013). Arabidopsis AP1 localizes to the TGN (Park et al, 2013;Wang et al, 2014), and mutants of the AP1M2 subunit are affected in the secretory and vacuolar transport pathways. In addition, trafficking of the essential SNARE KNOLLE from the TGN to the cell plate is impaired in dividing cells of ap1m2 mutants (Park et al, 2013).…”
Section: Adaptinsmentioning
confidence: 99%
“…The Arabidopsis genome encodes putative subunits of all five AP complexes (Happel et al, 2004;Hirst et al, 2011;Park et al, 2013). Arabidopsis AP1 localizes to the TGN (Park et al, 2013;Wang et al, 2014), and mutants of the AP1M2 subunit are affected in the secretory and vacuolar transport pathways. In addition, trafficking of the essential SNARE KNOLLE from the TGN to the cell plate is impaired in dividing cells of ap1m2 mutants (Park et al, 2013).…”
Section: Adaptinsmentioning
confidence: 99%
“…TaVIT1 also was found in the vacuolar membrane fraction, but based on higher abundance in the total fraction, it appeared that most of the TaVIT1 protein was targeted to other membranes. Closer inspection of the amino acid sequences revealed that TaVIT2 contains a universally conserved di-Leu motif for targeting to the vacuolar membrane (Bonifacino and Traub, 2003;Wang et al, 2014), which is absent from TaVIT1 (Supplemental Fig. S1B).…”
Section: Tavit2 Facilitates the Transport Of Iron And Manganesementioning
confidence: 99%
“…For each expressing construct, more than 20 individual cells were examined that represented .75% of the cells showing the same patterns or localizations. Pearson correlation coefficients were calculated using a Pearson and Spearman Correlation coefficients colocalization plug-in of the ImageJ program (National Institutes of Health; French et al, 2008;Wang et al, 2014;Gao et al, 2015). Images were processed via Adobe Photoshop as described previously (Jiang and Rogers, 1998).…”
Section: Transient Expressionmentioning
confidence: 99%
“…For secondary antibodies, Alexa Fluor-568 anti-rabbit or anti-rat (Molecular Probes) was used at 1:1,000 dilutions for immunodetection. Pearson correlation coefficients were calculated from more than five individual cells by using a PSC colocalization plug-in of the ImageJ program (French et al, 2008;Wang et al, 2014;Gao et al, 2015), which produced r values in the range of 21 to +1, with 0 indicating no discernible correlation, and +1 and 21 indicating strong positive or negative correlations, respectively.…”
mentioning
confidence: 99%